PEMANFAATAN AIR SUNGAI BERKELANJUTAN MELALUI INSTALASI POMPA HYDRAM DI SUNGAI CIKATOMEL - Fitri Hidayah Sundawati; Febby Fauziah; Rifi Wijayanti Dual Arifin; P Pandoe; Mohammad Nurdin; Dede Sujana; Ruli Ayu Setyowati (LPPM Universitas Nusa Mandiri, 2026)
Water availability in Desa Mekar Saluyu has become increasingly unstable due to seasonal variability and land‑use change that reduces infiltration and baseflow. This community service program implemented a hydraulic ram pump (hydram) on the Cikatomel River as an off‑grid water‑lifting technology for irrigation and non-consumtive domestic reserves. The Program combined technical installation with community capacity strengthening through site survey and discharge measurement, hydraulic–mechanical design and fabrication, installation with simple civil works, community training, and field evaluation. The potential beneficiaries include approximately 200 farmers, with a village agricultural area of around 400 ha, but the initial service trial focused on a 120 m distribution line. The driving discharge at the diversion weir was about 4 L/s. The delivery discharge achieved ±1.0–1.2 L/s with pump pressure around 2.1 bar and waste‑valve frequency 45–50 cycles/min, enabling an effective lift of about 25 m and potential daily volume of 86.4 to 103.7 m3 under continuous operation. The novelty of this program lies in the integration of hydram pump installation, a steel safety cage to protect the unit from river-related risk, and community-based operation and maintenance SOP coordinated with village officials. This activity improved initial access to water and highlighted the importance of local ownership, routine inspection, and watershed conservation for long-term system sustainability.